Optimal forest policies in an overlapping generations economy with timber and money bequests - Gregory S. Amacher; Erkki Koskela; Markku Ollikainen (The Research Institute of the Finnish Economy (ETLA), 2001)
This paper studies optimal forest policies in an overlapping generations forest economy with one-sided altruism, where timber and monetary bequests can be made across generations and forest amenities are a public good. We extend the existing economics literature by demonstrating that timber bequests can dominate money bequests in many situations, and that timber bequests may even be operative in dynamically inefficient steady states. We also characterize the optimal policy mix, which maximizes long run social welfare. This policy mix depends on the nature of the steady state equilibrium, and whether non-landowners have full access to forest stocks to enjoy amenities. The results support the argument that bequests and forest stocks must be considered jointly in determining first best and second best policies. Although these are often analyzed in isolation, we show that combinations of taxes and subsidies on harvesting and bequests may be efficient in a range of equilibria. The optimal policy mix we characterize in several types of steady states is not consistent with the choice governments typically make in practice.
Keywords: D64; Q23; H21; H23; 330; overlapping generations; timber bequest; altruism; forest taxation; Forstpolitik; Overlapping Generations; Erbe; Forststeuer; Theorie